Pembinaan Mahasiswa Prodi Pendidikan Agama Islam Yang Aktif Pada Organisasi Mahasiswa Iain Bone - Sultan Hasanuddin (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to find out how the guidance of active students of Islamic Education Major in IAIN Bone student organization is. The sources of data in this study were the Head of Islamic Education Major, Islamic Education Lecturers and the active students of Islamic Education Major in IAIN Bone student organization. Data collection methods are observation, interview and documentation. The collected data is then processed with quantitative descriptive analysis techniques. Data processing through three stages are data reduction, data presentation and conclusion drawing. The results showed that the development of Islamic Education Major of IAIN Bone is carried out starting from the individual students themselves. Supporting factors for the development of students of Islamic Education Major in IAIN Bone are organizational diversity and supporting facilities and infrastructures. Meanwhile, the factors that become obstacles are the individual of the student and coaching within the organization